GHG emission quantification for pavement construction projects using a process-based approach - Limsawasd, Charinee (Engineering and Applied Science Research, 2017)
Climate change and greenhouse gas (GHG) emissions have attracted much attention for their impacts upon the global environment. Initiating of new legislation and regulations for control of GHG emissions from the industrial sectors has been applied to address this problem. The transportation industries, which include operation of road pavement and pavement construction equipment, are the highest GHG-emitting sectors. This study presents a novel quantification model of GHG emissions of pavement construction using process-based analysis. The model is composed of five modules that evaluate GHG emissions. These are: material production and acquisition, (2) material transport to a project site, (3) heavy equipment use, (4) on-site machinery use, and, (5) on-site electricity use. The model was applied to a hypothetical pavement project to compare the environmental impacts of flexible and rigid pavement types during construction. The resulting model can be used for evaluation of environmental impacts, as well as for designing and planning highway pavement construction.